Small RNAs in plants: recent development and application for crop improvement - Kamthan, Ayushi; Chaudhuri, Abira; Kamthan, Mohan; Datta, Asis (Frontiers in Plant Science, 2015)
The phenomenon of RNA interference (RNAi) which involves sequence specific gene regulation by small non-coding RNAs i.e small interfering RNA (siRNA) and micro RNA (miRNA) has emerged as one of most powerful approaches for crop improvement. RNAi based on siRNA is one of the widely used tools of reverse genetics which aid in revealing gene functions in many species. This technology has been extensively applied to alter the gene expression in plants with an aim to achieve desirable traits. RNAi has been used for enhancing the crop yield and productivity by manipulating the gene involved in biomass, grain yield and enhanced shelf life of fruits & vegetables. It has also been applied for developing resistance against various biotic (bacteria, fungi, viruses, nematodes, insects) and abiotic stresses (drought, salinity, cold etc.). Nutritional improvements of crops have also been achieved by enriching the crops with essential amino acids, fatty acids, antioxidants and other nutrients beneficial for human health or by reducing allergens or anti-nutrients. Micro RNAs are key regulators of important plant processes like growth, development and response to various stresses. In spite of similarity in size (20-24nt), miRNA differ from siRNA in precursor structures, pathway of biogenesis, and modes of action. This review also highlights the miRNA based genetic modification technology where various miRNAs/artificial miRNAs and their targets can be utilized for improving several desirable plant traits. Micro RNA based strategies are much efficient than siRNA-based RNAi strategies due to its specificity and less undesirable off target effects. As per the FDA guidelines, small RNA based transgenics are much safer for consumption than those over expressing proteins. This review thereby summarizes the emerging advances and achievement in the field of small RNAs and its application for crop improvement.